2022
DOI: 10.1002/lio2.840
|View full text |Cite
|
Sign up to set email alerts
|

Reinke's edema management and voice outcomes

Abstract: Objectives Reinke's edema is a chronic disease of the respiratory tract that occurs in adults with a history of chronic smoke exposure. Also known as polypoid corditis, polypoid laryngitis, and polypoid degeneration of the vocal fold, it is strongly associated with smoking, frequently with vocal misuse/abuse, and occasionally with laryngopharyngeal reflux. Reinke's edema remains a cause of chronic dysphonia that is difficult to manage. This review provides perspectives on current and future management of Reink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 59 publications
0
17
0
3
Order By: Relevance
“…Cyclin E and CCND1 can bind to cyclin-dependent protein kinases to control cell cycle progression, such as the G1-S and G2-M transition [42,43]. The expression of Ki67 is closely associated with cell proliferation and growth and is commonly used as a proliferation marker in various tumor lesions [44,45]. The results of this study indicated a positive correlation between the expression levels of CDC23 and the genes CCNB1 and Ki67 during skeletal muscle satellite cell proliferation.…”
Section: Discussionmentioning
confidence: 61%
“…Cyclin E and CCND1 can bind to cyclin-dependent protein kinases to control cell cycle progression, such as the G1-S and G2-M transition [42,43]. The expression of Ki67 is closely associated with cell proliferation and growth and is commonly used as a proliferation marker in various tumor lesions [44,45]. The results of this study indicated a positive correlation between the expression levels of CDC23 and the genes CCNB1 and Ki67 during skeletal muscle satellite cell proliferation.…”
Section: Discussionmentioning
confidence: 61%
“…Chmiel i in., 2009;Barry, Vaezi, 2010;Milaniuk i in., 2015, s. 18-21]. Hoffman, 2022;Miłoński, 2022, s. 191-193]. Zmiany obrzękowe są często wynikiem długotrwałego współdziałania wymienionych czynników.…”
Section: Etiologia I Epidemiologia Reunclassified
“…In the management of RE, smoking cessation, anti-reflux medication, and voice therapy are recommended to help reduce the edema; however, patients whose voice quality does not improve with these therapies need surgery. To ensure improved voice rehabilitation after surgery, it is essential to continue voice therapy and anti-reflux treatment for a long period and avoid smoking ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different degrees of dysphonia are seen in patients with RE. It has also been noted that patients could develop dyspnea depending on the extent of the edema and the airway obstruction ( 7 ). The most typical symptoms in these patients are thickening of the voice, vocal fatigue, a reduced vocal range, and the inability to produce high-pitched voices.…”
Section: Introductionmentioning
confidence: 99%